Физические основы прогноза внезапных выбросов угля и газа - Стариков, Г.П. (Физико-технические проблемы горного производства, 2008)
Досліджувалась вільна енергія системи вугілля – газ та вплив на неї хвилі розвантаження. Обґрунтований та апробований критерій прогнозу викидів вугілля та газу. Free energy of a system containing coal-gas mixture is studied. An influence on the system from the unload wave is investigated also. A criterion for a prediction of the coal and gas bursts is developed and tested.